Step-by-step explanation:
-3+2y<4x
then
2y< 4x+ 3 (add both sides with 3)
y < 2x +3/2 ( divide both sides by 2 that is positif and we do not change the sens < )
Hope you understand.
Step-by-step explanation:
We have been given that David, Egil and Frances share money in the ratio 2:7:9.
Let 2x, 7x and 9x be the amounts of money that David, Agil and Frances get respectively.
We are told that Frances gets $80 more than David. So we can write this information in an equation as:
![9x=2x+80](https://tex.z-dn.net/?f=9x%3D2x%2B80)
Now let us solve for x.
![9x-2x=80](https://tex.z-dn.net/?f=9x-2x%3D80)
![7x=80](https://tex.z-dn.net/?f=7x%3D80)
Now let us substitute
in 7x (amount of money that Egil gets).
![\text{ Amount of money that Egil will get}=7\cdot \frac{80}{7}](https://tex.z-dn.net/?f=%5Ctext%7B%20Amount%20of%20money%20that%20Egil%20will%20get%7D%3D7%5Ccdot%20%5Cfrac%7B80%7D%7B7%7D)
Upon cancelling out 7 from numerator and denominator we will get,
Therefore, Egil will get $80.
Plug in zero for x to find the x intercept. So 3(0)-4y=2.
=-4y=2. Y=-1/2. X int. = (0,-1/2)
Answer:
answer becit uses b
Step-by-step explanation:
but yass queen but annyway
Answer: a,b,d,e are all right beacuse they all relate to the question
Step-by-step explanation:
c how ever is no shown on the graph and is therefor wrong